Expression Pattern of p62 in Primary Age-Related Tauopathy: Staging of p62 in PART - Wang, Xin; Zhang, Lei; Lu, Hui; Wu, Juanli; Liang, Huazheng; Sun, Bing; Zhu, Keqing (Frontiers in Aging Neuroscience, 2022)
The present study analyzed the distribution pattern of p62 in brains of primary age-related tauopathy (PART) and Braak NFT matched pre-AD and Alzheimer’s disease (AD) cases using immunohistochemistry in combination with semi-quantitative evaluation. In PART and AD brains, p62 was found positive in seven regions, including the neocortex, thalamus, basal ganglia, hippocampus, brainstem, cerebellar dentate gyrus and the cervical spinal cord. There was a positive correlation between the Braak NFT stage and the distribution of p62 expression. Six stages of p62 expression are proposed from the present study. Expression of p62 in the hippocampus of PART and AD was classified stage I, the brain stem stage II, the thalamus stage Ш, the basal ganglia stage IV, the neocortex stage V, the cerebellum and the cervical spinal cord stage VI. The hippocampus was the site initially affected by p62, especially the CA1 and the subiculum. They might be the earliest accumulation site of p62.